Intelektualisasi Islam dalam Paradigma Komplementatif Psikologi dan Akhlak Tasawuf Imam Al-Ghozali - M. Arifurrahman Hasyim; Thobib Al-Asyhar (Syifa al-Qulub, 2022)
Islam taught through indoctrination and dogmatism without developing and involving the potentials of intellectual nature has given birth to many problems in life. Islam as a belief system that is the foundation has turned into a rigid and irrational belief and has given birth to exclusive, even disruptive, behavior. Some so many people understand the teachings of Islam, but it does not at all reflect Islamic or moral behavior. This study uses a qualitative and complementary approach, which explores several theories from psychology and Sufism morality to analyze human behavior as a whole. This literature study research method will explore an in-depth problem analysis and produce descriptive-comprehensive conclusions. Imam Al-Ghozali became the primary theoretical basis regarding the relationship between the nature of the human soul and the intellectualization process in giving birth to moral behavior. Then, the beautiful face of Islam will appear through the intellectualization process with the paradigm of the pyramid of Sufism, which harmonizes the dimensions of Faith, Islam, and Ihsan in a perfect and balanced manner (i'tidal).